The influence of stickiness in sustaining development through zakat institutions in Malaysia - Mhd. Sarif, Suhaimi (Lembaga Zakat Negeri Kedah, 2020)
The influence of stickiness in sustaining development through zakat institutions in Malaysia is phenomenal and contextual. Both human and institutional factors are phenomenal and contextual to stickiness. Notably human factors are more apparent in attitude and commitment. Zakat institutions have essential role in attaining holistic economic and social development through United Nation’s Sustainable Development Goals 2030 with 17 goals. The main thesis is the magnitude of impact to the zakat recipients to the overall wellbeing of the society and the economy. The recipients among poor and needy remain status quo. The divide between the rich and the poor is getting wider. Inevitably, it leads non- sustainable development socially as well as economically. This study investigates the views of zakat officers on the stickiness issues and challenges in making the society and the economy performed and sustained. The study uses semi structured personal interview with the informants. The results of the interview argued that bureaucratic thinking, process and attitude contribute to lack of sustainability in the development of the society and the economy. The informants suggest for transformation on the bureaucratic thinking and attitude at zakat institutions in Malaysia.